1991
DOI: 10.1161/01.atv.11.4.844
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental contributions to cholesterol and its subfractions in 11-year-old twins. The Medical College of Virginia Twin Study.

Abstract: We conducted a cross-sectional analysis of the genetic and environmental contributions to the variance of lipoprotein cholesterol and its subfractions in children during early adolescence. Univariate path analysis was used to determine the relative contributions of genes, individual environment, and family environment to these measures in 233 11-year-old Caucasian twin pairs. For high density lipoprotein, high density lipoprotein 2 , low density lipoprotein, very low density lipoprotein, and triglycerides, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

1993
1993
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…No obvious age trend in heritability estimates can be detected from Table 1. Heritabilities measured before 39 and during 29 puberty are highly similar, and they remain fairly constant during early adulthood and middle age. Only in the elderly do heritabilities seem to decrease.…”
Section: Twin Studiesmentioning
confidence: 87%
“…No obvious age trend in heritability estimates can be detected from Table 1. Heritabilities measured before 39 and during 29 puberty are highly similar, and they remain fairly constant during early adulthood and middle age. Only in the elderly do heritabilities seem to decrease.…”
Section: Twin Studiesmentioning
confidence: 87%
“…Sex differences in heritabilities were also reported for triglycerides in a family study [Towne et al, 1993]. In contrast, other family studies have reported no sex differences for lipids and apolipoproteins [Bodurtha et al, 1991;Boomsma et al, 1996]. Such inconsistencies in results could be due to design or type of the study, selection of the study material, or differences in exposures to environmental factors that may have an indirect impact on lipid and apolipoprotein levels (i.e., dietary habits, medication, etc.…”
Section: Introductionmentioning
confidence: 85%
“…Lipids are influenced by genetic factors as well as environmental factors. Twin studies (10,21,31) have shown that most heritabilities of lipids were between 30 and 80%. The heritability of TC has been estimated at 32–87%, and the estimates are 24–79% for HDL, 22–89% for LDL and 0–81% for TG; the TG estimates are more variable than for the other lipids and therefore environmental factors play an important role.…”
Section: Discussionmentioning
confidence: 99%
“…Twin studies of lipids have reported heritability estimates between 30 and 80% (16–20), and differences with age and sex. Some studies on children and adolescents (13,21–24) have reported lipid heritability estimates of >60%. There have been few studies investigating any changes in magnitude of genetic and environmental effects on lipids during childhood and adolescence.…”
Section: Introductionmentioning
confidence: 99%